Routes, interaction and exchange in the southern Maya area
1 online resource.
Keywords: "This book explores routes of interaction and exchange in the Southern Maya Area, a zone that had both short and long-distance trade and whose natural resources were exploited by merchants and rulers, colonists and entrepreneurs during Olmec, Teotihuacan, Maya, Aztec, colonial and modern times. The book presents the research of both archaeologists and art historians to identify routes of interconnection, to demonstrate the strategic importance of settlements and ritual locations, and assess the significance of modes and mediums of exchange. The contributors employ innovative approaches, making use of state-of-the art technologies to reproduce and analyze the archaeological landscape (e.g. LiDAR, GIS, and Least Cost Path Analysis) and to source and characterize archaeological materials (e.g. Neutron Activation Analysis (NAA), X-Ray Fluorescence analysis [XRF] and Strontium analysis). The book combines these innovative approaches with earlier data sources and past analyses to develop a new, synthetic analysis of interaction. Routes, Interaction and Exchange in the Southern Maya Area will appeal to professional academics, students, and interested lay readers from a broad range of social science fields including anthropology, archaeology, geography, economics, history and art-history and is appropriate for undergraduate and graduate courses in Mesoamerican Archaeology"--